Arsenic Contamination: Africa the Missing Gap - Fatoki, O.S.; Akinsoji, O.S.; Ximba, B.J.; Olujimi, O.; Ayanda, O.S. (Asian Journal of Chemistry, 2013)
Arsenic is becoming a major challenge around the world due to its effect on human health. The World Health Organization set the standard for arsenic as 10 μg/L but most country do not adhere to this but rather still work with old standard of 50 μg/L. A lot of research has been carried out in different part of the world to determine the level of contamination. Europe has been able to reduce the effect of arsenic to the extent that it is almost non existence. Other continents are also trying to reduce the effect of arsenic and this can be seen from the number of research that has been reported. However, Africa is behind in this regard and not much data can be obtained on arsenic pollution or contamination. There is therefore a need for a thorough monitoring of arsenic in Africa so as to have a true picture of the level of arsenic contamination in Africa.